Worker energy recovery: A psychological approach - Solf Zárate, Arturo (2023)
The basic characteristics of the analysis of human resources centered on the concept of personal energy are presented, as well as certain strategies that allow workers to recover their physical, mental and emotional level, after the daily wear and tear when performing their functions. In addition, it inquires about the “Emotional Work”. The document is mainly aimed at psychologistsand other professionals who provide services to labor organizations giving priority to human resources.